2010
DOI: 10.2298/vsp1012007v
|View full text |Cite
|
Sign up to set email alerts
|

Recent views on cytohistological characteristics and pathogenic mechanisms of atherosclerotic lesions types I, II and III

Abstract: nem

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In this cell population, cells that demonstrate an immunohistochemical response to α-SMA, vimentin, and S100 protein are present. According to the literature data, as well as to the results of our previous research, immunoreactivity to α-SMA is a common characteristic of vascular smooth muscle cells, while immunoreactivity to vimentin, in the absence of immunoreactivity to desmin as a marker of highly differentiated contractile phenotype, suggests that smooth muscle cells of the synthetic phenotype are in question (Vukovic et al, 2010). It is also observed that these synthetically active smooth muscle cells demonstrate immunoreactivity to S100 protein, which we will consider separately.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In this cell population, cells that demonstrate an immunohistochemical response to α-SMA, vimentin, and S100 protein are present. According to the literature data, as well as to the results of our previous research, immunoreactivity to α-SMA is a common characteristic of vascular smooth muscle cells, while immunoreactivity to vimentin, in the absence of immunoreactivity to desmin as a marker of highly differentiated contractile phenotype, suggests that smooth muscle cells of the synthetic phenotype are in question (Vukovic et al, 2010). It is also observed that these synthetically active smooth muscle cells demonstrate immunoreactivity to S100 protein, which we will consider separately.…”
Section: Discussionmentioning
confidence: 62%
“…We have already mentioned that the target molecule of S100100 / S100A9 protein complex is the intermediate filament vimentin, which would suggest that its expression, occurred due to the loss of contractile characteristics of smooth muscle cells derived from mesenchyme, presents a predisposing factor for protein binding and further promoting cell migration, proliferation and differentiation. This complex also demonstrates marked susceptibility to oxidation, probably having a bifunctional, proinflammatory or antiinflammatory role, depending on its own redox status - (Gould et al, 1986;Libby, 1996;Donato et al;Vukovic et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Cellular population (10)(11)(12). The principal cell of the connective tissue is fibroblast because it produces elements of the extracellular matrix and the reticular lamina of the basement membrane as well (9).…”
Section: Organization Of the Connective Tissue In The Vascular Wallmentioning
confidence: 99%
“…This causes loss of elasticity. Elastic fibers are produced by fibroblasts and smooth muscle cell with synthetic phenotype (11,12). According to the degree of maturity, there are three types of elastic fibers: oxytalan, elaunin and mature fibers (49,50).…”
Section: Connective Tissue Fibers In the Wall Of The Blood Vesselsmentioning
confidence: 99%